PERANCANGAN INOVASI SEPATU DAN SELOP SEBAGAI SOLUSI MASYARAKAT MOBILITAS TINGGI DENGAN METODE QUALITY FUNCTION DEPLOYMENT - Tio Sampurno; Niramaya Yakshanti (Universitas Islam Indonesia, 2013)
In order to improve the quality of the society with high mobilityit needs an footwear innovation. With the behavior of a mobile society it must act effectively and efficiently organize belongings, especially the users who feel the hassle of carrying equipment. So that users think of some alternatives to travel, but the alternative is actually getting some disadvantages. Based on a survey of 30 respondents (students, faculty and young executives) 100% said that shoes and sandals should be two in one designed to be effective and efficient in travel frequently and 30 respondents also prefer sandals slippers as a model to the sole / bottom (section bottom of the shoes) than slippers. Based on the results of the questionnaire was obtained new footwear design innovation. This product is designed to utilize sol / bottom (the bottom of the shoe) at the shoe. it use to be slippers so that when Se-Top split, sol can be slippers. Meanwhile, when it was merged with the hood / upper (the top of the shoe) will be the shoes.